2001
DOI: 10.1177/002215540104901005
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic Reticulum Membrane-sorting Protein of Lymphocytes (BAP31) Is Highly Expressed in Neurons and Discrete Endocrine Cells

Abstract: S U M M A R YBAP31 is a transmembrane protein that associates with nascent membrane proteins in transit between endoplasmic reticulum (ER) and cis -Golgi. Its C-terminal dilysine (KKEE) motif, mediating return to the ER, is consistent with a role in early sorting of membrane proteins. An initiator caspase-binding site in the C-terminal domain of BAP31 is implicated in cytoplasmic membrane fragmentation events of apoptosis. Although BAP31 RNA is ubiquitous, the protein's anatomic localization has not been deter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0
2

Year Published

2003
2003
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(24 citation statements)
references
References 33 publications
2
20
0
2
Order By: Relevance
“…It has a cytoplasmic C terminus containing ␣-helical domains and a terminal dilysine ER-homing motif (26). Although cloning of human and murine cDNA showed that BAP31 is ubiquitously expressed in all tissues (26), BAP31 protein expression seems restricted to a minority of cells in tissues (35). In the present study, we have demonstrated the presence of BAP31 in human intestinal epithelial cells and PMN.…”
Section: Bap31 Associates With Cd11b/cd18mentioning
confidence: 47%
See 2 more Smart Citations
“…It has a cytoplasmic C terminus containing ␣-helical domains and a terminal dilysine ER-homing motif (26). Although cloning of human and murine cDNA showed that BAP31 is ubiquitously expressed in all tissues (26), BAP31 protein expression seems restricted to a minority of cells in tissues (35). In the present study, we have demonstrated the presence of BAP31 in human intestinal epithelial cells and PMN.…”
Section: Bap31 Associates With Cd11b/cd18mentioning
confidence: 47%
“…Previous studies on BAP31 have suggested that BAP31 is a component of the rough ER and ER-derived trafficking vesicles. It mainly localizes within ERlike structures and has been proposed to participate in regulating the export of selected membrane proteins from the ER to the Golgi apparatus (28,29,35,50). The localization pattern of BAP31 observed in human colonic epithelial cells would argue that BAP31 might also be involved in protein sorting or vesicle transport to cell basolateral surfaces.…”
Section: Bap31 Associates With Cd11b/cd18mentioning
confidence: 99%
See 1 more Smart Citation
“…22 Interestingly, Bap31 expression is highest in neurons, lymphocytes, and endocrine cells. 31 Future investigations will reveal to what extent the interactions of these variant DED-containing proteins are relevant for BARmediated neuroprotection.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies showed that overexpression of BAP31 increases the cell surface level of class I major histocompatibility complex (MHC) molecules [19]. BAP31 is very important in general cell processes including early secretory pathway trafficking of proteins and regulating the export of selected membrane proteins to the Golgi apparatus [18,20]. Additionally, as a mediator of apoptosis, full-length BAP31 acts as an inhibitor of apoptosis.…”
Section: Discussionmentioning
confidence: 99%